Study the radiation attenuation properties of ball clay-cement- iron slag composites by experimental and theoretical methods. (November 2022) - Almatari, M.; Dong, M.G.; Almousa, Nouf; Sayyed, M.I.; Khandaker, Mayeen Uddin; Alrashedi, M.F.; Saleh, I.H.; Elsafi, M.
Abstract: This study examined the radiation shielding features of ball clay-cement-iron slag as an alternative to concrete. Using a variety of cement, ball clay, and iron slag compositions, six samples were fabricated. The linear attenuation coefficient (LAC) was experimentally reported using three point sources (Am-241, Cs-137and Co-60) and a HPGe detector. The results show that the LACExp and LACXCOM values for the ball clay-cement-iron slag composites harmonized well. For the composite, the difference between the LAC values for the composite, 0.06 MeV, is notable; at the same time, they are almost negligible at 0.662 and 1.173 MeV. At 0.06 MeV, the difference between the LAC, from C1 and C6 is 0.56; yet, it is only 0.017 and 0.013 at 0.662 and 1.173 MeV. The LAC results confirm that adding iron slag to the prepared composites has a positive impact on their radiation attenuation competence. The composite's half value layer (HVL) at 0.06 MeV is reduced by about half when the iron slag content changes by 50 w.t%. According to the HVL results, the current alteration to iron slag contents reduces the influence of gamma photons. Highlights: The LAC of ball clay-cement- iron slag composites were reported. A good harmony was reported between the LACExp and LACXCOM values. The Zeff for the prepared ball clay-cement- iron slag composites were determined. The LAC was increased with adding iron slag to the composites.